2013
DOI: 10.1111/fwb.12300
|View full text |Cite
|
Sign up to set email alerts
|

Detrital nutrient content determines growth rate and elemental composition of bromeliad‐dwelling insects

Abstract: Summary In many aquatic ecosystems, detritus is the main basal resource and is able to support highly productive food webs. However, detritus is a relatively poor‐quality resource compared with living plants. Despite substantial research on how the nutrient content of living plants limits herbivores, there is little information on whether the nitrogen (N) and/or phosphorus (P) content of plant detritus similarly limits detritivore performance, especially under natural conditions. We examined this question by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 72 publications
6
59
0
Order By: Relevance
“…Whereas the N requirements of the spiders in our study were based on body elemental content, it is important to recall that silk production requires the allocation of large amounts of N (Craig, 2003), and therefore, web chemical content and web investment (i.e., silk amount) are a very likely factor influencing the N requirements of web‐building spiders (Savory, 1960; Vollrath, 2005) and other silk‐producing organisms, such as caddisflies (González, Romero, & Srivastava, 2014). Web‐building spiders show significant differences in the N content of silk, with tangle having 13.2%N, orbs 15.8%N, and sheet‐tangle 15.5%N in their webs (ALG, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the N requirements of the spiders in our study were based on body elemental content, it is important to recall that silk production requires the allocation of large amounts of N (Craig, 2003), and therefore, web chemical content and web investment (i.e., silk amount) are a very likely factor influencing the N requirements of web‐building spiders (Savory, 1960; Vollrath, 2005) and other silk‐producing organisms, such as caddisflies (González, Romero, & Srivastava, 2014). Web‐building spiders show significant differences in the N content of silk, with tangle having 13.2%N, orbs 15.8%N, and sheet‐tangle 15.5%N in their webs (ALG, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…However, the volume of water and the amount of FPOM, which are important variables for the colonization process (Kitching, 2000;Armbruster et al, 2002;Dézerald et al, 2015b), did not differ between treatments and contributed to the high similarity of the communities sampled throughout the experiment. These results differ from those found in studies developed in tropical forest ecosystems (Montero et al, 2010;González et al, 2014) and are probably related to the characteristics of restinga (i.e., less dense vegetation composed of species adapted to low water availability and high temperatures and solar radiation) (Zaluar and Scarano, 2000;Scarano, 2002). Some studies have suggested the volume of water is the main factor that influences the colonization of phytotelm ecosystems because it determines habitat size and susceptibility to colonization (Srivastava et al, 2008;Dézerald et al, 2014;Gossner et al, 2016).…”
Section: Shadedmentioning
confidence: 76%
“…Although CPOM represents an important energy source in many aquatic ecosystems (Vannote et al, 1980), typical invertebrate shredders were not found in the communities sampled. Organisms assigned to this functional feeding group have been observed in bromeliads of forest ecosystems (see Montero et al, 2010;Marino et al, 2012;González et al, 2014). Shredders are important to aquatic food webs because they provide food to other consumers (Graça, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although growth on a DRY leaf diet was reduced, it was not significantly lower than on the PERM diet. This result was unexpected given the lower ingestion rates and N concentration in leaves, which has been related to dampened growth rates in caddisflies (Iversen 1974;González et al 2014;Frainer et al 2016). Because leaves rapidly lose large quantities of fatty acids (including polyunsaturated and essential fatty acids) during decomposition in streams (Torres-Ruiz and Wehr 2010), more labile C, such as essential fatty acids and carbohydrates, might have , and dry flow (DRY, only for leaves)] on consumers' (Stenophylax and Physella, respectively) relative consumption rate (RCR; a n = 9-10 and c n = 6-9) and relative growth rate (RGR; b n = 10 and d n = 8-10).…”
Section: Discussionmentioning
confidence: 98%